Terapi Non Farmakologi dalam Pengendalian Tekanan Darah pada Pasien Hipertensi - Putra, Mardhiyanto Azhary; Nurhikmawati, Nurhikmawati; Khalid, Nur Fadhillah; Wiriansya, Edward Pandu; Arifuddin, Abdul Mubdi Ardiansar (Rumah Sakit Ibnu Sina, Makassar, 2024)
Changes in the pattern of communicable diseases to non-communicable diseases are classified as non-communicable diseases that do not cause scanning effects on other people and are a major factor in disorders of the blood vessels and chronic kidney disease, namely hypertension. Consumption of antihypertensive drugs continuously for a long time is not controlled and can increase the occurrence of Drug Related Problems (DRP). DRP is an effect experienced by the patient due to the involvement of the choice of treatment therapy used by the patient and is actually able to have an impact on the patient's condition such as non-adherence to drug consumption, drug side effects, or allergies that arise due to the drug consumed. This is proof that other alternative therapies are needed that are able to reduce the risk of dependence on drugs in maintaining the quality of life of people with hypertension, so the authors made a Literature Review on